2011
DOI: 10.1007/s00011-011-0320-y
|View full text |Cite
|
Sign up to set email alerts
|

Green tea polyphenols avert chronic inflammation-induced myocardial fibrosis of female rats

Abstract: GTP attenuates myocardial fibrosis through a suppression of chronic inflammation and innate immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Recent studies have shown that EGCG inhibits telomere attrition mediated cardiomyocyte apoptosis in cardiac hypertrophy (Sheng et al 2012). In addition, green tea polyphenols attenuate myocardial fibrosis through a suppression of chronic inflammation and innate immune responses (Shen et al 2011). Using freshly isolated single heart myocytes, green tea extract was found to protect cardiomyocytes from post-ischemia-reperfusion injury by preventing cytosolic Ca 2+ overload, myofibril disruption, and alterations in adherens and gap junction protein expression and distribution (Liou et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that EGCG inhibits telomere attrition mediated cardiomyocyte apoptosis in cardiac hypertrophy (Sheng et al 2012). In addition, green tea polyphenols attenuate myocardial fibrosis through a suppression of chronic inflammation and innate immune responses (Shen et al 2011). Using freshly isolated single heart myocytes, green tea extract was found to protect cardiomyocytes from post-ischemia-reperfusion injury by preventing cytosolic Ca 2+ overload, myofibril disruption, and alterations in adherens and gap junction protein expression and distribution (Liou et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological, clinical, and experimental studies have established a wide range of pharmacological effects of green tea catechins on cardiovascular diseases [9]. Catechins, mainly EGCG, exert vascular protective effects through multiple mechanisms, including antioxidative, anti-inflammatory, and anti-proliferative effects [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo part of this study showed that EGCG inhibited neutrophil recruitment, inflammation-driven angiogenesis, and pulmonary fibrosis. Yet another in vivo study completed by Shen et al [27] demonstrated that fibrosis in female rats caused by chronic inflammation was significantly reduced when treated with GT catechins. Regulatory T cells (T-reg) are essential in maintaining immune functions by targeting sites of sustained inflammation [28].…”
Section: Inflammationmentioning
confidence: 99%